2014
DOI: 10.2147/ott.s67556
|View full text |Cite
|
Sign up to set email alerts
|

The effects of ponatinib, a multi-targeted tyrosine kinase inhibitor, against human U87 malignant glioblastoma cells

Abstract: Glioblastoma is one of the most common malignant tumors in the nervous system in both adult and pediatric patients. Studies suggest that abnormal activation of receptor tyrosine kinases contributes to pathological development of glioblastoma. However, current therapies targeting tyrosine kinase receptors have poor therapeutic outcomes. Here, we examined anticancer effects of ponatinib, a multi-targeted tyrosine kinase inhibitor, on glioblastoma cells both in the U87MG cell line and in the mouse xenograft model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 38 publications
1
16
0
Order By: Relevance
“…Drugs targeting FGFR-TACC fusion genes have shown promising therapeutic potential in several types of cancer models, while clinical trials are still ongoing. To date, preclinical studies have shown a reduction of tumor growth and an increase of apoptosis upon treatment with the pan-FGFR inhibitor ponatinib in the U87MG cell line and the mouse xenograft model, suggesting a potential application of ponatinib as a chemotherapeutic option against GBM cells [60] . A phase II clinical trial studying ponatinib on recurrent GBM is now ongoing ( NCT02478164 ); however, it is not specifically designed for FGFR fusion–positive patients.…”
Section: The Landscape Of Gene Fusions In Subtypes Of Malignant Gliommentioning
confidence: 99%
“…Drugs targeting FGFR-TACC fusion genes have shown promising therapeutic potential in several types of cancer models, while clinical trials are still ongoing. To date, preclinical studies have shown a reduction of tumor growth and an increase of apoptosis upon treatment with the pan-FGFR inhibitor ponatinib in the U87MG cell line and the mouse xenograft model, suggesting a potential application of ponatinib as a chemotherapeutic option against GBM cells [60] . A phase II clinical trial studying ponatinib on recurrent GBM is now ongoing ( NCT02478164 ); however, it is not specifically designed for FGFR fusion–positive patients.…”
Section: The Landscape Of Gene Fusions In Subtypes Of Malignant Gliommentioning
confidence: 99%
“…It was shown to significantly inhibit tumor growth in in vitro and in vivo models of glioblastoma multiforme [73] and acute myeloid leukemia [74]. To elucidate the in vitro and in vivo efficacy of ponatinib, Garner and colleagues assessed the drug across a panel of GIST cell lines derived from patients with varying mutational statuses [75].…”
Section: Kit and Pdgfra Inhibitorsmentioning
confidence: 99%
“… 41 While ponatinib has not been tested in oligodendrogliomas, it has been shown to have in vitro activity against glioblastoma cells and has caused tumor reduction and apoptosis in a murine xenograft glioblasoma model. 23 Importantly, in a murine model, ponatinib demonstrated excellent CNS penetration with a brain to plasma concentration ratio of 0.88. 22 The ability of ponatinib to cross the BBB and achieve levels that are above in vitro IC 50 levels ultimately influenced the decision to pursue treatment with ponatinib rather than pazopanib.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the promising preclinical data suggesting effective in vitro and in vivo activity against glioblastoma cells and the promising characteristics of ponatinib to penetrate the central nervous system (CNS), as well a case report describing ponatinib use in a pediatric patient, we ultimately decided to initiate ponatinib for this patient. 20 23 The patient weighed 75 kg and was initially started on a treatment regimen of 15 mg of ponatinib daily, with a goal dose of 45 mg orally. After 2 months, the patient’s dose was increased to 30 mg daily for the second cycle.…”
Section: Case Reportmentioning
confidence: 99%